Invading macrophages play a major role in the liver progenitor cell response to chronic liver injury - Viebahn, C.; Benseler, V.; Holz, L.; Elsegood, Caryn; Vo, M.; Bertolino, P.; Ganss, R.; Yeoh, G. (Elsevier BV, 2010)
Background & Aims: Although a strong association between liver progenitor cells (LPCs) and inflammation exists in many chronic liver diseases, the exact role of the immune system in LPC-mediated hepatic regeneration remains unclear. A number of pro-inflammatory factors were identified in cytokine knockout mice in which the LPC response was attenuated but neither the mechanism nor the producing cells are known. Methods: To identify the critical immune cells and cytokines required in the LPC response, we compared two diet-induced models of liver injury with two recently established transgenic models of immune-mediated hepatitis. Results: Despite severe inflammation being observed in all models, the generation of LPCs was highly dependent on the cause and kinetics of liver damage. The LPC response was associated with an increase of macrophages and CD8+ T cells but not natural killer cells. T cell-deficient mice were able to mount a LPC response, albeit delayed, suggesting that T cells are not essential. Mice mounting an LPC response showed elevated numbers of Kupffer cells and invading CX3CR1 highCCR2high macrophages secreting persistent high levels of tumour necrosis factor alpha (TNFa), a major cytokine involved in the LPC response. Conclusions: Liver macrophages are an important determinant of LPC expansion during liver regeneration in models of diet- and immune-mediated liver injury. Invading macrophages in particular provide pro-mitogenic cytokines such as TNFa that underpin the process. LPC themselves are a source of chemokines (CCL2, CX3CL1) that attract infiltrating macrophages. © 2010 European Association for the Study of the Liver. Published by Elsevier B.V. All rights reserved.